Molecular determinants of neuroprotection in blood-brain interfaces of the cynomolgus monkey - Strazielle, Nathalie; Blondel, Sandrine; Confais, Joachim; El Khoury, Rita; Contamin, Hugues; Ghersi-Egea, Jean-François (Frontiers in Pharmacology, 2025)
The blood-brain barrier (BBB) formed by the cerebral microvessel endothelium and the blood-CSF barrier (BCSFB) formed by the choroid plexus epithelium impact the cerebral bioavailability of drugs and endogenous molecules that contribute to neuroinflammatory and neurodegenerative diseases. Species specificities in tight junction proteins and efflux transporters governing the barrier functions of these interfaces hamper the direct translation of pharmacokinetic and pathophysiological data from rodents to human. We defined the molecular composition of tight junctions and identified the efflux transporters present at the BBB and BCSFB of cynomolgus monkey to assess whether this species is a relevant alternative to rodents. Choroid plexuses, cerebral microvessels, cortex and cerebellum were isolated from adult cynomolgus monkeys, and analysed by RT-qPCR and immunohistochemistry. Results were compared with data available in the literature for rat and human. In monkeys as in rat and human, claudin-5 in the BBB and claudin-1, -2, -3 in the BCSFB were landmark tight junction proteins. ABCB1 was strictly associated with the BBB, and ABCC1 was predominant at the BCSFB compared to the BBB. The monkey, like human, differed from rat by the localization of ABCG2 protein in choroidal vessels, a low expression of ABCC4 and SLC22A8 in the BBB, and the presence of SLC47A1 at the BCSFB. While the main characteristics of brain barriers are common to all three species, cynomolgus monkey and human share specificities in the expression and localization of selected claudins and efflux transporters that are not met in rat.